2017
DOI: 10.1177/1099800417715907
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Positive and Negative Symptom Domains in Schizophrenia

Abstract: Schizophrenia is a highly heritable disorder, the genetic etiology of which has been well established. Yet despite significant advances in genetics research, the pathophysiological mechanisms of this disorder largely remain unknown. This gap has been attributed to the complexity of the polygenic disorder, which has a heterogeneous clinical profile. Examining the genetic basis of schizophrenia subphenotypes, such as those based on particular symptoms, is thus a useful strategy for decoding the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 125 publications
0
19
0
Order By: Relevance
“…In addition, general cognitive ability has been found to be genetically correlated with schizophrenia at approximately −0.58 (Blokland et al, 2017). Less research has focused on the genetic effects on symptom severity, but one recent metaanalysis of five sibling studies found that negative symptoms (h 2 = 0.34), disorganized symptoms (h 2 = 0.56), and positive symptoms (h 2 = 0.36) were all significantly heritable (p < .0001; Rietkerk et al, 2008), whereas the results from genetic association studies are less consistent (e.g., Xavier & Vorderstrasse, 2017). In a similar vein to symptom severity, the substantial amount of work regarding community functioning in schizophrenia has infrequently focused on the role of genetic effects, although several family studies have found global functioning to be significantly correlated among first-degree relatives, with heritability estimates between 0.50 and 0.68% (e.g., Cardno et al, 1998;Kendler et al, 1997;Kuo et al, 2018;McGrath et al, 2009;Vassos et al, 2008).…”
Section: Genetic Effects On Symptom Severity Cognition and Communmentioning
confidence: 99%
“…In addition, general cognitive ability has been found to be genetically correlated with schizophrenia at approximately −0.58 (Blokland et al, 2017). Less research has focused on the genetic effects on symptom severity, but one recent metaanalysis of five sibling studies found that negative symptoms (h 2 = 0.34), disorganized symptoms (h 2 = 0.56), and positive symptoms (h 2 = 0.36) were all significantly heritable (p < .0001; Rietkerk et al, 2008), whereas the results from genetic association studies are less consistent (e.g., Xavier & Vorderstrasse, 2017). In a similar vein to symptom severity, the substantial amount of work regarding community functioning in schizophrenia has infrequently focused on the role of genetic effects, although several family studies have found global functioning to be significantly correlated among first-degree relatives, with heritability estimates between 0.50 and 0.68% (e.g., Cardno et al, 1998;Kendler et al, 1997;Kuo et al, 2018;McGrath et al, 2009;Vassos et al, 2008).…”
Section: Genetic Effects On Symptom Severity Cognition and Communmentioning
confidence: 99%
“…Reviewed studies are also based on correlation analysis, which is believed not to be a strong measure of association between predictors and outcomes 36 . Besides, these primary studies vary in terms of study population and use of assessment tools, scoring and standardization techniques, and have several limitations, such as small sample size, short duration of follow-up and limited use of data from healthy siblings and/or controls 9 , 37 , 38 . Of interest, none of these reviews fully addressed evidence from both longitudinal and cross-sectional data-driven studies on schizophrenia symptoms and cognitive deficits among patients with schizophrenia spectrum disorders, relatives and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons of inconsistencies are the heterogeneity of study population, high symptomatic variability between patients and within patients over time, use of various assessment tools, use of different clustering algorithms, and use of different scoring and standardization techniques. 13,18,37 The major limitations are small sample size, short duration of follow-up, and limited used of data from healthy siblings and/or controls. 37 All these factors blur our understanding of the heterogeneity of the course of schizophrenia.…”
Section: Tackling Heterogeneity In Schizophreniamentioning
confidence: 99%
“…[7][8][9][10][11][12] The prevalence of negative symptoms is 50-90% in first-episode psychosis and persists in 20-40% of patients with schizophrenia. [13][14][15] Cognitive deficits affects 75-80% of patients with schizophrenia. 16 The most common deficits occur in executive function, processing speed, memory (e.g.…”
Section: Introductionmentioning
confidence: 99%